Focal and Segmental Glomerulosclerosis and Membranous Nephropathy overlapping in a patient with Nephrotic Syndrome: a case report - Silva,Crislaine Aparecida da (2020)
Abstract Introduction: Some cases of membranous nephropathy (MGN) present focal segmental glomerulosclerosis (FSGS) typically associated with disease progression. However, we report a case of a patient who seemed to have MGN and FSGS, both primary. Case presentation: A 17-year-old female, Caucasian, presenting lower extremity edema associated with episodes of foamy urine and high blood pressure, had physical and laboratorial exams indicating nephrotic syndrome. A renal biopsy was performed and focal and segmental glomerulosclerosis were observed under light microscopy in some glomeruli presented as tip lesion, and in others it was accompanied by podocyte hypertrophy and podocyte detachment in urinary space, compatible with podocytopathy FSGS. Besides, there were thickened capillary loops with basement membrane irregularities due to "spikes" compatible with MGN stage II. Immunofluorescence showed finely granular IgG, IgG4, and PLA2R deposits in capillary loops and, in electron microscopy, subepithelial deposits and foot process effacement. These morphological findings are compatible with FSGS and MGN stage II. Conclusions: In the present case, clinical and morphological characteristics showed a possible overlap of primary FSGS and MGN as focal and segmental glomerulosclerosis does not seem to be related with MGN progression but with the podocytopathy FSGS.